Risks of venous thromboembolic complications in related to combined oral contraceptives - K. A. Gabelova; N. A. Shabanova; V. F. Bezhenar; E. E. Zvartau; Yu. A. Akishina (IRBIS LLC, 2022)
Hormonal contraception is the most popular and effective reversible method for preventing unwanted pregnancy exerting multiple prophylactic and therapeutic effect along with contraceptive activity. The main adverse coupled to combined oral contraceptives (COCs) is its impact on the hemostasis and increased risk of venous thromboembolic complications. A great evolutionary path has been travelled after beginning application of hormonal contraception to reduce dose of its estrogen component and improving quality of gestagen component. Nevertheless, thrombotic complications related to COCs use still remain a pressing issue not only due to disease severity and high mortality rate from pulmonary embolism (PE), but also due to the difficulties in its timely diagnostics. Here we describe a clinical case of a 19-year-old patient suffering from vena cava inferior thrombosis complicated by PE after using COCs.